Investigations toward a Non‐Aqueous Hybrid Redox‐Flow Battery with a Manganese‐Based Anolyte and Catholyte. Issue 24 (24th May 2021) - Schmucker, Maximilian; Gully, Tyler A.; Schmidt, Alexei; Schmidt, Benjamin; Bromberger, Kolja; Disch, Joey; Butschke, Burkhard; Burgenmeister, Benedikt; Sonnenberg, Karsten; Riedel, Sebastian; Krossing, Ingo
Abstract: A new all‐Manganese flow battery (all‐MFB) as a non‐aqueous hybrid redox‐flow battery is reported. The discharged active material [Cat]2 [Mn II Cl4 ] (Cat =  organic cation) utilized in both half‐cells supports a long cycle life. The reversible oxidation of [Mn II Cl4 ] 2− to [Mn III Cl5 ] 2− at the positive electrode and manganese metal deposition from [Mn II Cl4 ] 2− at the negative electrode give a cell voltage of 2.59 V. Suitable electrolytes are prepared and optimized, followed by a characterization in static battery cells and in a pumped flow‐cell. Several electrode materials, solvents, and membranes are tested for their feasibility in the all‐MFB. An electrolyte consisting of [EMP]2 [MnCl4 ] and some solvent γ‐butyrolactone is cycled 500 times, both in a static as well as a flow‐cell, over a period of two months, with coulombic efficiencies up to 83%. With the electrolytes prepared in this work, energy densities up to 74 Wh L −1 are possible, exceeding the VRFB benchmark system, using solely the cheap and abundant element manganese as the active material. Although further optimizations are necessary, this system represents a new and promising setup toward sustainable stationary energy storage. Abstract : An all‐manganese hybrid redox‐flow battery, a new system with high energy density is described. The same active material, based on the cheap and abundant element manganese is used in both half‐cells, which supports a long lifetime. With 500 cycles achieved in a flow‐cell, this new chemistry for non‐aqueous redox‐flow batteries is very promising.